2023
DOI: 10.1108/aaaj-07-2021-5341
|View full text |Cite
|
Sign up to set email alerts
|

Monetization of politics and public procurement in Ghana

Abstract: PurposeThis paper aims to investigate the prevalence of corruption in Ghana to understand how and why it has turned public procurement into a mere money-making scheme instead of a means to provide needed public goods and services.Design/methodology/approachThe study focuses on Ghana as a case study and mobilizes the monetization of politics lenses. Data are collected via interviews with key officials across the procurement sector (including the government, donors and civil society), documents, documentaries an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…This may not be surprising due to other factors such as rule-mending, rule-breaking and breaches of procurement laws, among others. These empirical observations in the study are consistent with these works (Osei-Tutu et al , 2009; Akomah and Nani, 2018; Amagnya, 2023; Lassou et al , 2023).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This may not be surprising due to other factors such as rule-mending, rule-breaking and breaches of procurement laws, among others. These empirical observations in the study are consistent with these works (Osei-Tutu et al , 2009; Akomah and Nani, 2018; Amagnya, 2023; Lassou et al , 2023).…”
Section: Discussionsupporting
confidence: 93%
“…These administrative challenges were identified at the local government level: low professionalism in procurement, especially contractors and suppliers; red-tape (overbureaucratization); incidences or acts of bribery and corruption; and too much political interference (Osei-Tutu et al , 2010; Adusei and Awunyo-Vitor, 2015). Other administrative lapses or flaws occur when some tender processes opt to go through open competitive tendering and end up as single-source or sole-sourcing without the approval of the regulatory authority, the Public Procurement Authority (PEFA, 2018, 2013; Boatemaa-Yeboah and Tamakloe, 2019; Lassou et al , 2023). The work of Osei-Tutu et al (2009) identified favoritism and nepotism as key factors that inhibit Ghana’s efforts toward achieving VfM in the procurement of goods, services and works.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation